Revolution of new energy industry: Spatio-temporal dynamics and drivers of technological diffusion in Zhejiang, China - Liu, Jie; Chen, Tao; Chen, Ziyi (Frontiers in Environmental Science, 2022)
The new energy that aims to reduce pollution is the technological trend of energy development in the future. The development of the new energy industry is a complex system. Studying the spatio-temporal revolution of new energy industry helps analyse the development trend, supply, and demand of new energy. Thus, taking Zhejiang Province as an example, the spatial evolution of the new energy industry from 2016 to 2021 is studied. The evolution trend of spatial agglomeration of the new energy industry shows the coexistence of agglomeration and diffusion. No overall agglomeration of the new energy industry in Zhejiang Province is observed. The development performs solid spatial dependence. The results indicate that it is challenging to aggregate resources and achieves economies of scale without a leading enterprise. The diffusion of new energy technologies in the future depends on industrial agglomeration and the cultivation of leading enterprises.